If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -90 = 3x + 5x + -10 Reorder the terms: -90 = -10 + 3x + 5x Combine like terms: 3x + 5x = 8x -90 = -10 + 8x Solving -90 = -10 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -90 + -8x = -10 + 8x + -8x Combine like terms: 8x + -8x = 0 -90 + -8x = -10 + 0 -90 + -8x = -10 Add '90' to each side of the equation. -90 + 90 + -8x = -10 + 90 Combine like terms: -90 + 90 = 0 0 + -8x = -10 + 90 -8x = -10 + 90 Combine like terms: -10 + 90 = 80 -8x = 80 Divide each side by '-8'. x = -10 Simplifying x = -10
| f(3)=-3x | | 5x+3(2x-9)=-21 | | y+1=2(x-4) | | Y-4=0.7(x-3.5) | | -6(-2x-2)=108 | | 3s+-5=-11 | | x-4x=6x+18 | | -3x+9=5x-71 | | 3(1+2x)=-6x+87 | | 5x-7=9+1 | | -2x+4x-33=9 | | Y-3.5=0.7(x-4) | | -4x+3=3-6x | | -4X-6Y+2Z=-2 | | n2+5=15 | | f(-1)=-3x | | -4(5m+20)=-400 | | 12-6z=2x+15 | | 7x+19=21 | | 6X+9Y-3Z=3 | | 3(3)(-3)-8(2)-3= | | -z^4+17z^2-16=0 | | 8c-71=12c-72-4c | | 3(-3+2x)=3x+3 | | 7(-2x-4)=-168 | | -(-2)+2(2.1)-(-2)= | | 51x-.83x^2=0 | | 2X+3Y-2=1 | | x^2*x=2 | | 3g+5wheng=4 | | 4y-5=-2x-31 | | 5X+Y-3Z=1 |